Creative integration of Egyptian cultural heritage in electric vehicle styling - Yousif, Tamer; Ramirez, Mariano; Shawqi, Maha (Creativity Studies, 2025)
This paper explores the integration of Egyptian cultural heritage into electric vehicle design, aligning with Egypt Vision 2030 principles. The purpose is to investigate how ancient Egyptian symbols can inspire innovative electric vehicle styling and assess the educational outcomes of such a design project. Conducted as a coursework project at the October 6 University in Giza, 6 of October, Egypt, this initiative challenged product design students to design electric vehicle’s using symbols and motifs used in ancient Egyptian civilization. The methodology included four phases: 1) research and inspiration; 2) ideation and refinement; 3) digital modelling, and 4) physical modelling. The findings showed that integrating cultural symbols enhanced the aesthetic and symbolic value of the electric vehicle’s, fostering creativity and deeper cultural appreciation among students. Practical implications suggest that such designs can appeal to consumers seeking unique and culturally meaningful products. The originality and value of this paper lie in demonstrating how cultural heritage can be preserved and promoted through contemporary design, contributing to both educational outcomes and market innovation.